2019
DOI: 10.21203/rs.2.18975/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pregnancy outcomes, early separation and psychiatric relapse experienced by South African women with peripartum psychosis: A descriptive exploration

Abstract: Background: The peripartum period is associated with increased incidence of severe mental illness (SMI), with a greater occurrence of psychotic symptoms and psychiatric admissions. There has been little research on South African mothers with peripartum psychosis to examine what factors contribute to their experiences of pregnancy and the postpartum period. This study aimed to explore the relevant socio-demographic factors and pregnancy outcomes in order to determine focus areas for intervention. Methods: Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The presence of mental illness in a partner or family member should also be cited as demographic factors [ 40 ]. Data collected in South Africa indicate socio-demographic problems and psychoactive substance use as risk factors [ 70 ].…”
Section: Neurobiological and Psychosocial Problems As Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of mental illness in a partner or family member should also be cited as demographic factors [ 40 ]. Data collected in South Africa indicate socio-demographic problems and psychoactive substance use as risk factors [ 70 ].…”
Section: Neurobiological and Psychosocial Problems As Risk Factorsmentioning
confidence: 99%
“…It is necessary to search for environmental and cultural causes of PP-related infanticide [ 84 ]. There are no reliable data on the prevalence of PP in Africa, where it is a serious problem [ 70 ].…”
Section: Symptomatology Of Postpartum Psychosismentioning
confidence: 99%
“…Data on the prevalence of psychosis in pregnancy is limited in Africa owing to lack of studies. Previous studies addressing this topical issue have focused on the factors contributing to the development of mental health issues, including psychosis, post-delivery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the foregoing suggests that studies elucidating PLEs in pregnancy are extremely important, our understanding of psychosis risk in pregnancy is limited largely because the existing studies have overwhelmingly focused on persons who have been diagnosed with psychotic disorders [ 5 , 8 10 ]. For example, in their study involving 40 mothers diagnosed postpartum psychosis in South Africa, Voges et al found that substance use during pregnancy, postpartum abuse and lifetime experience of trauma were reported by the participants [ 6 ]. Understanding the prevalence and correlates of PLEs in the perinatal period can strategically support healthcare professionals in their effort to render basic mental health services to pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…While the foregoing suggests that studies elucidating PLEs in pregnancy are extremely important, our understanding of psychosis risk in pregnancy is limited largely because the existing studies have overwhelmingly focused on persons who have been diagnosed with psychotic disorders [5,[8][9][10]. For example, in their study involving 40 mothers diagnosed postpartum psychosis in South Africa, Voges et al found that substance use during pregnancy, postpartum abuse and lifetime experience of trauma were reported by the participants [6]. Understanding the prevalence and correlates of PLEs in the perinatal period can strategically support healthcare professionals in their effort to render basic mental health services to pregnant women.…”
Section: Introductionmentioning
confidence: 99%